Effects of Elevated CO2 on Nutritional Quality of Vegetables: A Review - Dong, Jinlong; Gruda, Nazim; Lam, Shu K.; Li, Xun; Duan, Zengqiang (Frontiers in Plant Science, 2018)
Elevated atmospheric CO2 (eCO2) enhances the yield of vegetables and could also affect their nutritional quality. We conducted a meta-analysis using 57 articles consisting of 1,015 observations and found that eCO2 increased the concentrations of fructose, glucose, total soluble sugar, total antioxidant capacity, total phenols, total flavonoids, ascorbic acid, and calcium in the edible part of vegetables by 14.2%, 13.2%, 17.5%, 59.0%, 8.9%, 45.5%, 9.5%, and 8.2%, respectively, but decreased the concentrations of protein, nitrate, magnesium, iron, and zinc by 9.5%, 18.0%, 9.2%, 16.0%, and 9.4%. The concentrations of titratable acidity, total chlorophyll, carotenoids, lycopene, anthocyanins, phosphorus, potassium, sulfur, copper, and manganese were not affected by eCO2. Furthermore, we propose several approaches to improving vegetable quality based on the interaction of eCO2 with various factors, including species, cultivars, CO2 levels, growth stages, light, O3 stress, nutrient, and salinity. Finally, we present a summary of the eCO2 impact on the quality of three widely cultivated crops, namely, lettuce, tomato, and potato.